Theoretical Computer Science 8th IFIP TC 1/WG 2.2 International Conference, TCS 2014, Rome, Italy, September 1-3, 2014. Proceedings - Diaz, Josep; Lanese, Ivan; Sangiorgi, Davide (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 8th FIP WG 2.2 International Conference, TCS 2014, held in Rome, Italy, in September 2014. The 26 revised full papers presented, together with two invited talks, were carefully reviewed and selected from 73 submissions. [Suggestion--please check and add more if needed] TCS-2014 consisted of two tracks, with separate program committees, which dealt respectively with: - Track A: Algorithms, Complexity and Models of Computation, and - Track B: Logic, Semantics, Specification and Verification.